AI Hallucination: Pentingnya Literasi dan Berpikir Kritis dalam Pendidikan Hukum - Rahman, Rafika Rizky Aulia; Zatika, Dinda Anna; Malida, Reisa; Yanis, Adam Muhammad (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2025)
This activity was conducted to foster literacy awareness and critical thinking skills among law students in the era of Artificial Intelligence (AI) utilization. The activity was motivated by the growing reliance of students on AI in the learning process, which potentially diminishes their capacity for deep reading and legal reasoning. The participants consisted of law students in the City of Bandar Lampung with varying levels of reading habits. Through a series of counseling sessions, discussions, and reflective practices, this activity explored the relationship between legal literacy, critical thinking skills, and the ethics of AI usage.The results indicate that legal literacy is not merely related to the number of books read but also to the depth of understanding, interpretation, and contextualization of legal texts within their social framework. Furthermore, participants were introduced to the risks of over-reliance on AI and the phenomenon of AI hallucination, which may compromise the accuracy and integrity of legal reasoning. The discussions were then directed toward strengthening students’ competencies through the integration of human analytical skills and AI-based technologies in a reflective and ethical manner.